Competitiveness Analysis of Main Agri-Food Products - Ion Laurentiu Petre; Claudiu Tudorache; Marco Platania; Andra Mecu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
This paper analyses the competitiveness of the main Romanian agri-food products on the international market, using the Competitiveness Index that includes the components of market performance and gross value. The results show that Romania has a competitive advantage for cereals, wheat, maize, legumes and sheep meat, where per capita production exceeds domestic and global consumption. However, certain products such as rice, tomatoes and beef have a sub-unit index, reflecting a reduced value competitiveness against the global market. In addition, the decrease in subsidies and the demographic decline are factors that can negatively influence competitiveness. The conclusions emphasize the need for supportive policies to maintain and improve the performance of the Romanian agri-food sector in the long term.